Nlrp12 mutation causes C57BL/6J strain-specific defect in neutrophil recruitment - Tyler K. Ulland (Nature Portfolio, 2016)
The role of NLRP12 in immunity to bacterial infection is controversial as varied and contrasting results have been published using C57BL/6 mice. Here the authors shed light on this issue, showing that unlike C57BL/6N mice, C57BL/6J mice have a missense point mutation in NLRP12 that is associated with defective neutrophil recruitment.